Glycoproteomic and Lipidomic Characterization of Industrially Produced Whey Protein Phospholipid Concentrate with Emphasis on Antimicrobial Xanthine Oxidase, Oxylipins and Small Milk Fat Globules - Gulustan Ozturk; Nuanyi Liang; Mrittika Bhattacharya; Randall C. Robinson; Shalini Shankar; Yu-Ping Huang; Bruna Paviani; Ameer Y. Taha; Daniela Barile (Dairy, 2022)
This work investigates the composition of whey protein phospholipid concentrate (WPPC), an underutilized dairy stream, and reveals that it is a source of many bioactive compounds that can benefit the immune system and gut health. Our glycoproteomics approach uncovered that proteins derived from the milk fat globule membrane (MFGM) represent 23% of the total protein relative abundance and identified 85 N-glycans. Released sialic acid, an additional marker of glycosylation, ranged from 1.2 to 2% of the total weight. Xanthine oxidase, a glycosylated marker of MFG bioactivity, was found in high abundance and displayed higher antimicrobial activity than bovine milk, despite its similar fat and solids content. An average MFG diameter of 2.64 ± 0.01 µm was found in liquid WPPC, compared to 4.78 ± 0.13 µm in bovine milk, which likely explains the unusually high presence of glycosylated membrane-bound proteins and phospholipids, whose total fatty acids accounted for 20% of the WPPC total fatty acid pool. Free and bound oxylipins (mainly derived from linoleic acid) were also identified, together with other less abundant anti-inflammatory lipid mediators derived from eicosapentaenoic acid and docosahexaenoic acid. Our study demonstrates that WPPC represents a promising starting material for bioactive compound extraction and a functional vehicle for the delivery of small MFGs.